Fish Encounters: Aquariums and their Veterinarians in a Rapidly Changing World - Braverman, Irus (Humanimalia, 2019)
The extensive body of social science and humanities scholarship on zoos rarely discusses aquariums. Despite their independent historical trajectory and unique characteristics and challenges, aquariums are typically considered the younger sister to the more established terrestrial zoo institutions. This article is an initial exploration of modern public aquariums through the eyes of these institutions’ veterinarians, a small but rapidly growing, and quite influential, professional cohort. Drawing on in-depth interviews with a handful of aquarium veterinarians in various sites — including the United States, Canada, Israel, Portugal, Denmark, and Germany — the article documents some of the everyday challenges that these medical practitioners face when attempting to manage the health and wellbeing of captive marine animals. Their feet in several worlds, aquarium veterinarians must balance their medical training and animal welfare sensibilities with the specific nature of the aquatic animals under their care, and also with the understanding of their evolving responsibilities toward ocean conservation. For these professionals, the rights-welfare-conservation approaches to animal care are not abstract ideas but rather real-life situations that dictate their actual modes of practice in caring for marine animals. This can only be an initial study and thus highlights the need for additional scholarly work in the social sciences and humanities on aquariums, their wet forms of life, and the challenges— as well as the opportunities — that their management poses to the human caretakers of this space. This scholarly need is especially acute in light of the declining state of extant species and ecosystems in the world’s seas. Public aquariums and their veterinarians will arguably perform increasingly important roles in the conservation of our blue planet.